The mediating role of customer relationship management between e-supply chain management and competitive advantage - Abdalrazzaq Aloqool (Growing Science, 2022)
The purpose of this study is to explore the role of implementing e-supply chain management (E-SCM) on the competitive position of companies and whether implementing customer relationship management (CRM) can affect the relationship between E-SCM and competitive advantage. To achieve this objective, a quantitative approach was utilized. A total of 300 questionnaires were distributed where 243 questionnaires were returned, with 17 incomplete questionnaires being excluded, leaving 226 usable questionnaires. PLS-SEM software was used to analyze the data. The results of this study demonstrate the imperative role of implementing E-SCM and CRM on creating a competitive advantage for firms. It also shows that CRM mediates the relationship between E-SCM and competitive advantage, suggesting that utilizing different technologies can help firms better communicate with their customers and thus better serve them which in turn will enhance customers’ satisfaction and thus boost the competitive position of the firm.